2021
DOI: 10.3390/ijms22157908
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Proteomic and Metabolomic Analysis of Human Osteoblasts, Differentiated from Dental Pulp Stem Cells, Hinted Crucial Signaling Pathways Promoting Osteogenesis

Abstract: Population aging has been a global trend for the last decades, which increases the pressure to develop new cell-based or drug-based therapies, including those that may cure bone diseases. To understand molecular processes that underlie bone development and turnover, we followed osteogenic differentiation of human dental pulp stem cells (DPSCs) using a specific induction medium. The differentiation process imitating in vivo osteogenesis is triggered by various signaling pathways and is associated with massive p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 121 publications
0
3
0
Order By: Relevance
“…Pathway analysis showed that aminoacyl–tRNA biosynthesis and porphyrin and chlorophyll metabolism pathways were associated with multiple dental disorders. Previous metabolomic data have shown that aminoacyl–tRNA biosynthesis promotes osteogenic differentiation (Novakova et al 2021), which may lead to alveolar bone resorption and eventually increase the risk of tooth loss. Evidence has shown that the metabolic profile of periapical periodontitis is related to this pathway, which supports our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Pathway analysis showed that aminoacyl–tRNA biosynthesis and porphyrin and chlorophyll metabolism pathways were associated with multiple dental disorders. Previous metabolomic data have shown that aminoacyl–tRNA biosynthesis promotes osteogenic differentiation (Novakova et al 2021), which may lead to alveolar bone resorption and eventually increase the risk of tooth loss. Evidence has shown that the metabolic profile of periapical periodontitis is related to this pathway, which supports our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Aminoacyl‐tRNA has been shown to promote osteodifferentiation, stimulate protein synthesis in osteoblastic cells, and accelerate osteoblastic bone formation (Aleidi et al, 2021). The stimulation of protein synthesis by aminoacyl‐tRNA could lead to the acceleration of bone recovery in rats with both fractures and TBI (Nováková et al, 2021). These mechanisms were also consistent with our metabolic profile analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The potential of metabolites as significant indicators in the diagnosis, treatment, and prognosis of various diseases has been gradually recognized (Zahoor et al, 2022). The advantages of metabolomics and ultra‐high performance liquid chromatography–quadrupole time‐of‐flight MS (UHPLC–Q‐TOF/MS) not only lie in their high sensitivity but also in their capability to comprehensively measure endogenous small‐molecular metabolites in tissues, blood, cells, and other samples (Nováková et al, 2021). They can provide a snapshot of the metabolic state of an organism at a particular time, revealing insights into normal biological processes, as well as pathological states and environmental stresses.…”
Section: Introductionmentioning
confidence: 99%
“…For this to occur, mechanical signals are propagated in the nucleus for regulation of the state of chromatin and transcription, where the synthesis of aminoacyl-tRNA plays a critical role [48]. In a recent combined proteomic and metabolomic analysis relating to osteogenic differentiation of dental pulp stem cells, a four-fold increase in protein levels of aminoacyl-tRNA synthetase was found [60]. Consistently, our data suggest that osteogenic differentiation was enhanced in stiff ECMs and that aminoacyl-tRNA synthesis was increased, which indicates that aminoacyl-tRNA may be related to induced osteogenesis in stiff ECMs.…”
Section: Metabolite Set Enrichment Analysis and Metabolic Pathway Ana...mentioning
confidence: 99%